Leaf-like carbon nanotube-graphene nanoribbon hybrid reinforcements for enhanced load transfer in copper matrix composites. (September 2017) - Yang, Ming; Weng, Lin; Zhu, Hanxing; Zhang, Fan; Fan, Tongxiang; Zhang, Di
Abstract: A leaf-inspired nanoengineering is employed for the structural design of carbon nanofillers. We fabricate leaf-like carbon nanotube (CNT )-graphene nanoribbon (GNR ) hybrids as novel reinforcements for a copper matrix composite. The straight and stiff CNT 'midribs' are conducive to individual dispersion whilst the two-dimensional GNR 'margins' provide more sufficient interface contact area and deformation gradient zone, giving rise to significantly improved interfacial load transfer and mechanical strength as compared to the unmodified nanotubes. The mechanics and strengthening mechanisms are further rationalized by finite element analysis and the generalized shear-lag theory. Graphical abstract: